Understanding How Intelligent Process Automation Impacts Business Continuity: Mapping IEEE/2755:2020 and ISO/22301:2019 - Jose Cascais Bras; Ruben Filipe Pereira; Sergio Moro; Isaias Scalabrin Bianchi; Rui Ribeiro (IEEE Access, 2023)
Organizations have been responding to possible disruptions in the organization and, at the same time, trying to increase customer satisfaction through digitising their processes. Thus, Intelligent Process Automation has been catching the latest trends in intelligent process automation due to the ease of use associated with data and requirements compliance; intelligent process automation is a step above regular automation as it mimics human behaviours and thought patterns to automate intelligently streamlines workflows and business processes. However, the constant introduction of technology via process automation in organizations can have positive and negative impacts on business continuity that need to be addressed. Although there are recent best practices, frameworks, guidelines, and standards, few studies focus on the relationship between these realms. The relationship between two sets of requirements, one for implementation practice and management methodology for intelligent software-based process automation, found in IEEE 2755.2-2020 and the other, ISO 22301-2019, about the business, to implement, maintain, and improve a management system to protect, reduce the likelihood of occurrence, prepare, respond, and recover from outages when they arise. This research is integrated into forthcoming areas for investigating the interplay between intelligent process automation and the continuity of business operations. Both are analysed and explained so that users can develop intelligent software-based process automation that complies with both frameworks in a way to embed continuity practices in an organization while optimizing business processes using Intelligent Process Automation. The study provides a bi-directional mapping for IEEE 2755.2:2020 and ISO 22301:2019, along with introducing a visual model to enhance their utility. It offers versatile applications, benefiting a wide range of stakeholders.